Newcastle Disease Virus Expressing Human Immunodeficiency Virus Type 1 Envelope Glycoprotein Induces Strong Mucosal and Serum Antibody Responses in Guinea Pigs - Khattar, Sunil K. (American Society for Microbiology, 2011)
Human immunodeficiency virus type 1 (HIV-1) is transmitted mainly through mucosal sites. Optimum strategies to elicit both systemic and mucosal immunity are critical for the development of vaccines against HIV-1. We therefore sought to evaluate the induction of systemic and mucosal immune responses by the use of Newcastle disease virus (NDV) as a vaccine vector. We generated a recombinant NDV, designated rLaSota/gp160, expressing the gp160 envelope (Env) protein of HIV-1 from an added gene. The gp160 protein expressed by rLaSota/gp160 virus was detected on an infected cell surface and was incorporated into the NDV virion. Biochemical studies showed that gp160 present in infected cells and in the virion formed a higher-order oligomer that retained recognition by conformationally sensitive monoclonal antibodies. Expression of gp160 did not increase the virulence of recombinant NDV (rNDV) strain LaSota. Guinea pigs were administered rLaSota/gp160 via the intranasal (i.n.) or intramuscular (i.m.) route in different prime-boost combinations. Systemic and mucosal antibody responses specific to the HIV-1 envelope protein were assessed in serum and vaginal washes, respectively. Two or three immunizations via the i.n. or i.m. route induced a more potent systemic and mucosal immune response than a single immunization by either route. Priming by the i.n. route was more immunogenic than by the i.m. route, and the same was true for the boosts. Furthermore, immunization with rLaSota/gp160 by any route or combination of routes induced a Th1-type response, as reflected by the induction of stronger antigen-specific IgG2a than IgG1 antibody responses. Additionally, i.n. immunization elicited a stronger neutralizing serum antibody response to laboratory-adapted HIV-1 strain MN.3. These data illustrate that it is feasible to use NDV as a vaccine vector to elicit potent humoral and mucosal responses to the HIV-1 envelope protein.